Ginsenoside Rg1 attenuates dextran sodium sulfate-induced ulcerative colitis in mice - Chen, Y; Zhang, Q; Sun, L; Liu, H; Feng, J; Li, J; Wang, Z (Physiological research, 2023)
Ulceration colitis (UC) is a chronic and recurrent inflammatory disorder in the gastro-intestinal tract. The purpose of our study is to explore the potential mechanisms of ginsenoside Rg1 (GS Rg1) on dextran sulfate sodium (DSS)-induced colitis in mice and lipopolysaccharide (LPS)-induced RAW 264.7 cells. Acute colitis was induced in male C57BL/6 mice. In vitro model of LPS-induced RAW 264.7 cells to simulate enteritis model. The disease activity index (DAI), colon length, body weight and histopathological analysis were performed in vivo. Pro-inflammatory cytokines and markers for oxidative and anti-oxidative stress, MPO level were measured in vivo and in vitro. Nuclear erythroid 2-related factor 2 (Nrf2) and NF-?B p65 protein levels were analyzed using western blotting. Our results indicated that the UC models were established successfully by drinking DSS water. GS Rg1 significantly attenuated UC-related symptoms, including preventing weight loss, decreasing DAI scores, and increasing colon length. GS Rg1 ameliorated the DSS-induced oxidative stress. IL-1beta, IL-6, and TNF-alpha levels were significantly increased in serum and cell supernatant effectively, while treatment with the GS Rg1 significantly reduced these factors. GS Rg1 reduced MPO content in the colon. GS Rg1 treatment increased SOD and decreased MDA levels in the serum, colon, and cell supernatant. GS Rg1 restored the Nrf-2/HO-1/NF-?B pathway in RAW 264.7 cells and UC mice, and these changes were blocked by Nrf-2 siRNA. Overall, GS Rg1 ameliorated inflammation and oxidative stress in colitis via Nrf-2/HO-1/NF-kappaB pathway. Thus, GS Rg1 could serve as a potential therapeutic agent for the treatment of UC.
Keywords: Animals; kolon; lipopolysacharidy; kolitida; ginsenosidy; Sulfates; Colon; sírany; síran dextranu; Mice; Dextran Sulfate; Ginsenosides; Dextrans; Lipopolysaccharides; dextrany; Colitis, Ulcerative; myši; Male; modely nemocí na zvířatech; ulcerózní kolitida; Colitis; Disease Models, Animal; NF-kappa B; zvířata; mužské pohlaví; Mice, Inbred C57BL; myši inbrední C57BL